IMPLEMENTASI MEDIA PEMBELAJARAN MISODO (MISTERI SOAL LUDO) DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK MADRASAH IBTIDAIYAH - Tolak Ready; Agus Kurnaidi; Yetti Hidayatillah (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
In this report there are several details or points to be able to provide a detailed explanation. The first explanation is about a main problem regarding the course of learning in educational institutions that we have researched, one of which is the course of learning that is the same (monotonous). The second step is the steps we use to achieve research, one of which is implementing the concepts in our observations in creating or creating a learning Media called (MISODO). The research method that the author uses is a quantitative method. Regarding the essence that becomes the description of the author's explanation, namely; implementation, name of learning media, problems (monotonous), and solutions to these.